Sulfonimidates: useful synthetic intermediates for sulfoximine synthesis via C–S bond formation - Matos, Priscilla Mendonça; Lewis, William; Moore, Jonathan C.; Stockman, Robert A. (ACS Publications, 2018)
The ever-increasing prevalence of sulfoximine derivatives in drug discovery programmes has brought about a renaissance in the development of methods for their synthesis. Sulfoximine synthesis via C-S bond formation however has been comparatively underexplored. Herein, we report that sulfonimidates constitute a versatile precursor for the synthesis of medicinally relevant sulfoximines.